Superheated Atomization: Influence of Nozzle Geometry on Mass Flux and Spray Characteristics - Wirth, Karl-Ernst; Günther, Astrid (Chemie Ingenieur Technik, 2012)
The atomization of superheated liquids utilizes thermal energy for partial evaporation of flow media, by this enhancing the spray disintegration. The degree of evaporation and the generation of big droplets is a function of the nozzle geometry. By analyzing mass fluxes and by application of optical measurement techniques geometry- dependent modifications of flow characteristics and spray morphology are investigated.
Keywords: Flow rate; Nozzle geometry; Optical measurement techniques; Spray